PENGARUH SENAM AEROBIK TERHADAP PERUBAHAN KADAR GULA DALAM DARAH PADA PASIEN DIABETES MELLITUS - Azizah, Fidrotin; Nurfain, Nurfain; Anggraini, Vera (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2018)
Diabetes mellitus is a condition where blood sugar levels exceed normal levels. In people with diabetes mellitus, physical exercise acts as a glycemic control that regulates and controls blood sugar levels. Physical exercise is one of them is aerobic exercise, which aims to improve and mantain the freshness of the body. The purpose of the study to determine the effect of aerobic exercise on changes in blood sugar levels in patients with diabetes mellitus.This research method used pre experimental one group pre post test design. The population is all people with diabetes mellitus in the working area of healt center nglumber following Prolanis activity in the year 2017 as many as 47. While the sampel is 23 respondent taken through purposive sampling technique. This study is conducted once a week for 3 weeks. Taking data using observation, then done editing, coding, scoring and tabulation of data in the analysis by using crosstab.Cross tabulation result obtained after aerobic gymnastics majority decreased blood sugar levels of 23 respondent (100%). So it can be concuded that there is influence of aerobic gymnastic on changes in blood sugar levels in patients with diabetes mellitus in the working area of healt center nglumber kepohbaru bojonegoro.From the description above is recommended for respondents to do aerobic exercise about 1 week, because aerobics aerobics have the benefits and benefits of them can lower sugar levels.